Quarantine cold treatment against Ceratitis capitata (Wiedemann)(Diptera: Tephritidae) to export clementine mandarins to Japan - Santaballa, E.=700 1 Laborda, R.; Cerda, M.
(Es, En)
Ilus., 10 ref.
Keywords: CITRUS RETICULATA; CERATITIS CAPITATA; ALMACENAMIENTO EN FRIO; CUARENTENA; EXPORTACIONES; JAPON; BOLETIN DE SANIDAD VEGETAL: PLAGAS